Unlocking the therapeutic potential of tumor-derived EVs in ischemia-reperfusion: a breakthrough perspective from glioma and stroke - Zhongnan Hao; Wenxin Guan; Wei Wei; Meihua Li; Zhipeng Xiao; Qinjian Sun; Yongli Pan; Wenqiang Xin (Journal of Neuroinflammation)
Abstract Clinical studies have revealed a bidirectional relationship between glioma and ischemic stroke, with evidence of spatial overlap between the two conditions. This connection arises from significant similarities in their pathological processes, including the regulation of cellular metabolism, inflammation, coagulation, hypoxia, angiogenesis, and neural repair, all of which involve common biological factors. A significant shared feature of both diseases is the crucial role of extracellular vesicles (EVs) in mediating intercellular communication. Extracellular vesicles, with their characteristic bilayer structure, encapsulate proteins, lipids, and nucleic acids, shielding them from enzymatic degradation by ribonucleases, deoxyribonucleases, and proteases. This structural protection facilitates long-distance intercellular communication in multicellular organisms. In gliomas, EVs are pivotal in intracranial signaling and shaping the tumor microenvironment. Importantly, the cargos carried by glioma-derived EVs closely align with the biological factors involved in ischemic stroke, underscoring the substantial impact of glioma on stroke pathology, particularly through the crucial roles of EVs as key mediators in this interaction. This review explores the pathological interplay between glioma and ischemic stroke, addressing clinical manifestations and pathophysiological processes across the stages of hypoxia, stroke onset, progression, and recovery, with a particular focus on the crucial role of EVs and their cargos in these interactions.